2020
DOI: 10.1089/neur.2020.0051
|View full text |Cite
|
Sign up to set email alerts
|

Differential Change in Oculomotor Performance among Female Collegiate Soccer Players versus Non-Contact Athletes from Pre- to Post-Season

Abstract: Sensitive and reliable tools are needed to evaluate potential behavioral and cognitive changes following head impact exposure in contact and collision sport participation. We evaluated change in oculomotor testing performance among female, varsity, collegiate athletes following variable exposure to head impacts across a season. Female, collegiate, contact sport (soccer, CONT) and non-contact sport (NON-CONT) athletes were assessed pre-season and post-season. Soccer athletes were grouped according to total seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 75 publications
(114 reference statements)
0
15
0
Order By: Relevance
“…28,[54][55][56] Further, results from this study are similar to those of a parallel longitudinal study of female soccer players, which showed that those with higher estimated exposure to head impacts demonstrated relative stability over time whereas those with lower estimated head injury exposure and non-contact controls showed faster reaction times at post-season relative to preseason on antisaccade and MGS tasks. 30 Unlike eye-movement testing results, there were no group-by-time effects observed on ImPACT testing in general or on the ImPACT reaction time or visual motor composite scores. Qualitatively, ImPACT composite scores improved from pre-to post-season on memory and visual motor composites among COLL groups and remained stable or improved more modestly among NON-COLL.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…28,[54][55][56] Further, results from this study are similar to those of a parallel longitudinal study of female soccer players, which showed that those with higher estimated exposure to head impacts demonstrated relative stability over time whereas those with lower estimated head injury exposure and non-contact controls showed faster reaction times at post-season relative to preseason on antisaccade and MGS tasks. 30 Unlike eye-movement testing results, there were no group-by-time effects observed on ImPACT testing in general or on the ImPACT reaction time or visual motor composite scores. Qualitatively, ImPACT composite scores improved from pre-to post-season on memory and visual motor composites among COLL groups and remained stable or improved more modestly among NON-COLL.…”
Section: Discussionmentioning
confidence: 70%
“…See Gallagher and colleagues for further details. 30 Immediate Post-Concussion Assessment and Cognitive Test. ImPACT is a 25-min computerized cognitive battery designed for ages 12-59, delivered by a secure Web portal.…”
Section: Participants and Recruitmentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, to our knowledge, little work has used the prosaccade task to investigate the differences in saccadic eye movements between skilled and less skilled players. Some studies using the prosaccade task only focus on examining the cognitive changes of players caused by head impact exposure in contact and collision sports ( Kiefer et al, 2018 ; Gallagher et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%